Association between success and unsuccess rates on technical skills and physical qualities in rugby players - Coghetto, G.; Zanrosso, E. M.; Rabello, R.; da Ros, J. L.; Rodrigues, R. (Research Quarterly for Exercise and Sport, 2023)
Purpose: Although physical and technical performance are both fundamental in rugby union teams, the association between these variables in sub-elite players is limited. This study investigated the association between the rate of success and unsuccess in technical skills throughout a season with physical quality variables in sub-elite rugby players. Methods: Twenty-five sub-elite rugby union players (age: 26.4 ± 3.8 years; body mass: 99.68 ± 14.34 kg; height: 1.81 ± 0.07 m) completed the following assessments: (i) broad jump; (ii) 10- and 30-meters sprint speed; (iii) 5-10-5 test; (iv) 1 RM of bench press, chin-up and squat and (v) Yo-Yo fitness test. The rate of success and unsuccess in tackles, attacking rucks and carries were measured during a season. Results: We found that: (i) higher success rates in carries were associated with faster speeds and greater broad jump distance; (ii) higher unsuccess rates in tackles were associated with lower 1 RM chin-up. When controlling for playing position, (iii) higher success rates in carries were associated with 30-meters speed and broad jump distance; (iv) higher success rates in tackles were associated with higher 1 RM chin-up; and (v) higher unsuccess rates in tackles were associated with lower 1 RM chin-up. Conclusions: Success and unsuccess rates in attacking rucks and success in carries were not associated with physical qualities. Therefore, training programs that improve speed, lower limb power and upper limb maximal strength should receive greater attention when seeking to achieve greater success in trying to break the opponent`s defensive line and stop the ball carrier.